Bank Domestic Outstandings in Central- Eastern-European Countries between 2008 and 2018 - Bozsik, Sándor; Gazda, Vladimir (Theory, Methodology, Practice – Review of Business and Management, 2018)
The economic crisis that broke out in the most developed part of the world in 2008 seriously affected the Central-Eastern-European bank systems. This was no wonder, because these economies were closely linked to the developed countries. Firstly, the Central-Eastern-European banks were mostly owned by large Western-European banks, and the management of these subsidiaries became tougher due to the asset management problems of their mother banks. The current paper examines the deleveraging of bank systems of this area during the crisis and thereafter. A special northern-southern division can be observed among the Central-Eastern-European banking systems, where the border is unfortunately at the northern border of Hungary. During the crisis, the amount of bank outstandings was mostly determined by the economic growth, the starting state of loan-deposit ratio, as well as the uncertainty of sovereign Credit Defalut Spread. In the aftercrisis period the change in outstandings is especially dependent on the non-performing loan ratio and the change in loandeposit ratio. Hungary is an “off-line” country for all strong correlated variable pairs, so the decrease in domestic outstandings may have country-specific reasons in addition to the general theoretical variables.